2011
DOI: 10.1016/j.pmrj.2011.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Associated With Posterior Tibial Tendon Pathology on Sonographic Assessment

Abstract: We present one of the largest studies on PTT pathology. PTT pathology can occur in the supramalleolar area, a region that often is not assessed on imaging. Although data are unavailable with regard to whether the natural history of supramalleolar PTT is different from that of other regions, patients with supramalleolar PTT pathology had more severe grades of tear and increased prevalence of tenosynovitis and were more often women. It is essential to recognize supramalleolar PTT pathology so that consequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Tears appear as clefts or gaps in a tendinotic tendon and are often associated with caliber alterations (38) (Fig 10). Dynamic US is useful in patients suspected of having friction syndrome at a thickened retinaculum and tendon instability related to flexor retinaculum disruption, which allows anterior tendon subluxation (29,38,42).…”
Section: Imaging Of Ptt Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tears appear as clefts or gaps in a tendinotic tendon and are often associated with caliber alterations (38) (Fig 10). Dynamic US is useful in patients suspected of having friction syndrome at a thickened retinaculum and tendon instability related to flexor retinaculum disruption, which allows anterior tendon subluxation (29,38,42).…”
Section: Imaging Of Ptt Degenerationmentioning
confidence: 99%
“…The type 3 tear is complete, producing a fluid-filled gap or segmental absence of the tendon (Fig 14). More than 90% of PTT tears involve the retromalleolar or inframalleolar tendon, with inframalleolar tearing (including insertional tearing at the navicular bone attachment) as the most common type (28,42). Supramalleolar tears and diffuse tearing of multiple segments of the tendon are seen less frequently (42).…”
Section: Imaging Of Ptt Degenerationmentioning
confidence: 99%
“…Jain et al reported that supramalleolar pathologies are likely to be severe and more often occur in women [19]. They also concluded that those patients have an increased prevalence of coexisting findings, such as tenosynovitis [19]. Hence, complete assessment of the entire course of the tendon is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were referred to our department after clinical examination by three experienced orthopaedic surgeons, who specialized in foot and ankle surgery (20,19, and 10 years of experience). Clinical inclusion criteria were: pain along the course of the PTT, localized edema, as well as asymmetric acquired flat foot deformity.…”
Section: Methodsmentioning
confidence: 99%
“…Posterior tibial tendon [12]: evidenced by resisted inversion movements. Peroneal tendons [13]: resisted subversion.…”
Section: Tendon Snapping Due To Instability Caused By Rupture Of the mentioning
confidence: 99%